Effect of Ethephon on Variation in Fiber and Vessel Structure in Wood of Acacia senegal (L.) Willd - Kanica Upadhyay; Pooja Kumari; S.B.S. Pandey; Anju Vijayan; Rahul Chopra; A.K. Gupta; S.K. Jat (Annals of Arid Zone, 2025)
Acacia senegal trees are economically valuable for their gum arabic production, supporting local economies and providing income for farmers. Gum production from these trees can be manyfold increased by ethephon application. The wood of these trees is composed of vessels, fibers, and wood rays, with fibers being the primary strength-providing element. This study investigated the anatomical properties of Acacia senegal wood from Jhalawar, Rajasthan, examining fiber and vessel dimensions as affected by ethephon application. The results showed that ethephon treatment had no significant impact on wood properties.